Feeling is the Secret - Goddard, Neville (Ascent Audio, 2015)
Your thoughts shape your life, create your reality, and ultimately limit or expand your true potential. Everything from relationships and love, to health and well-being, to wealth and prosperity are directly connected to how you think and what you think about most of the time. For better or for worse. A quick and easy read, Feeling is the Secret describes how our thoughts and feelings affect who we become and what we achieve. When we have the power to change them, we gain the power to change our circumstances, our health, and our life's purpose.